Growth response of the diatom Chaetoceros species to the elemental ratios of Deep Ocean waters. (31st August 2020) - Inbakandan, D.; Sriyutha Murthy, P.; Magesh Peter, D.; Vinithkumar, N.V.; Dharani, G.
Abstract: Phytoplankton production, succession and community composition is limited by nutrients, temperature and spectral properties. Elemental ratios serve as indicators for predicting productivity of phytoplankton including diatom . Deep ocean water (DOW) as a marine natural resource is rich in inorganic nutrients. In the present study, as part of the OTEC program, an initial attempt was made to characterize quantitatively the elemental ratios in DOW and relate to growth of the diatom, Chaetoceros sp. In addition, the production of Chaetoceros sp. in DOW was compared with a conventional nutrient enrichment medium, generally used for phytoplankton growth. To assess the productive ability of DOW, factorial experiments with Chaetoceros sp. were carried out with (i) unaltered DOW [100% DOW], (ii) admixtures [50:50] of DOW and surface seawater (SSW) [50% DOW], (iii) plain SSW, (iv) SSW enriched with nutrients and (v) DOW enriched with nutrients. Results of admixtures of seawater starting from 0% SSW to 100% DOW revealed optimum Redfield ratios at 50% dilution. Results on growth of Chaetoceros sp. in 100% DOW showed a sudden blooming on the 2nd and 3rd day. Chlorophyll 'a' values of 70 mg m −3 were obtained with DOW and SSW enriched with f/2 medium. Similarly with 50% DOW same chlorophyll 'a' concentrations was reached on the 4th 5th day and declined on the 6th day. Results of the present study demonstrate that 100% and 50% dilutions of DOW could be used for intensive culture of Chaetoceros sp. and that biomass production could be achieved within 3 days compared to incubations which use a conventional medium. Highlights: Levels of (nitrate, phosphate and silicate) nutrients increased with depth. DOW has the potential for culture of phytoplankton compared to conventional mediums. N: P ratio was found to be double in DOW from 1000 m depth. 100% and 50% dilutions of DOW could be used for intensive culture of phytoplankton.